Why would I be married here? : marriage migration and dispossession in neoliberal India - Kukreja, Reena (Cornell University Press, 2022)
"The book examines cross-region marriage migration in India that transgresses traditional norms of caste, religion, and ethnicity in marriage-making. An intimate account of the lived experience of migrant Hindu and Muslim brides in rural North India, it foregrounds the intersections of patriarchy, caste, religious fundamentalism, and neoliberal capitalism in shaping their everyday reality"--